Innovative approach to enhance active online learning: engagement, feedback and classroom environment / Chin Ying Liew, Li Li Voon and Siow Hoo Leong - Liew, Chin Ying; Voon, Li Li; Leong, Siow Hoo (Universiti Teknologi MARA, 2023)
In the community of inquiry (CoI) frameworks, a meaningful learning with technology in higher education requires interaction of social presence, cognitive presence, and teaching presence. However, it is challenging to create a CoI within an online teaching and learning (OTL) environment especially during the COVID-19 pandemic when educators are forced to conduct it. This paper proposes three innovative approaches for such a community to enhance active learning during synchronous OTL, specifically You Talk for engaging students, Resource Pool for facilitating feedback, and Classroom Meet for recreating the classroom environment. The three approaches were implemented by independent instructors for their respective undergraduates in synchronous online class. The treatment groups show significantly better academic performance than the control groups for all the three innovative approaches. The students from the treatment groups strongly agree that these innovative approaches promote active interaction, enhance attainment of the learning contents, deliver the course contents effectively, assure satisfaction and engage students actively during OTL. It suggests that either approach to engaging students, or facilitating feedback, or recreating the classroom environment serves as teaching presence to support the social presence of the students and therefore creates cognitive presence among them.